Rancang Bangun Game Edukasi Pengenalan Budaya Daerah Sebagai Pendukung Pelajaran SBDP di Sekolah Dasar - Ari Hidayatullah; Henri Septanto (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
This case study is expected to support the lessons in Arts, Culture, and Crafts (SBDP), where conventional teaching methods often fail to engage students, resulting in a limited understanding of cultural material. Therefore, the purpose of creating this game is to design and develop an educational game as a learning tool for SBDP and to introduce regional dances to enrich the learning process. By using the Game Development Life Cycle method, the game will present interactive and engaging material to increase students' interest in learning and understanding various traditional dances in Indonesia. Students will learn to recognize the names of dances from different regions, along with brief information about their places of origin, movement characteristics, and a short history